Implementation of the Independent Learning Independent Campus Program Policy (Case Study: Faculty of Social Sciences and Law, Makassar State University) - Alfarizy, Salman; Yamin, Muh Nur; S, Muh. Rizal (Universitas Negeri Makassar, 2025)
This study aims to find out how the implementation and determinant factors in the Independent Learning-Free Campus Program Policy (Case Study of the Faculty of Social Sciences and Law, State University of Makassar). This research uses a qualitative approach with descriptive methods. Data collection was carried out by field observations, interviews, documentation and literature study. Data analysis techniques use data collection, data condensation, data presentation and data verification or conclusions.The results of this study indicate that the Implementation of the Independent Campus Learning Program (Case Study: Faculty of Social Sciences and Law, Makassar State University) based on the indicators put forward by Van Meter and Van Horn (Tahir, 2014: 71-72) has not been fully met including, namely : Policy Standards and Targets, Resources, Interorganizational Communication and Activity Strengthening, Characteristics of Implementing Agencies, Economic Environment. Social and Politics, and the Attitude of the Executors.